Applying Sutureless Encircling Number 41 Band and Transscleral Chandelier-Assisted Laser Retinopexy for Scleral Buckling Procedure. (30th November 2017) - Gomaa, Amir Ramadan; Elbaha, Samir Mohamed
Abstract : Purpose . To assess the outcome of sutureless encirlcing number 41 band and transscleral laser retinopexy in uncomplicated rhegmatogenous retinal detachment (RRD), using a wide-angle viewing system (WAVS) and chandelier endoillumination. Methods . Prospective intervention study included 30 eyes of 30 patients presenting with RRD of recent onset indicated for SB. All cases were treated by sutureless encircling number 41 band and transscleral laser retinopexy. Visualization was provided by the Resight WAVS and a single 27-gauge chandelier endoillumination. Anatomical and visual outcomes were evaluated. Results . The mean age of our group was 49.8 ± 12.3 years, and the mean duration of RD was 7 (0–50) days. Twenty-four eyes (80.0%) were phakic while the remaining 6 eyes (20%) were either pseudophakic or aphakic. The primary retinal reattachment rate was 83.3% (25 out of 30 eyes). LogMAR visual acuity improved from 1.3 (0.30–2.0) preoperatively to 1.0 (0.40–1.60) at first month (p = 0.002 ) and to 0.70 (0.20–1.92) at third month (p < 0.001 ). Conclusion . Sutureless encircling number 41 band with chandelier-assisted transscleral laser retinopexy is a safe and effective technique for managing uncomplicated RRD. It provides a high primary success rate while eliminating the complications of cryotherapy, sutures, and broad buckles.